The Influence of Motivation and Work Spirit on Job Satisfaction of Civil Servants at the Public Works and Spatial Planning Office for Housing and Settlement Areas in Kubu Raya Regency - Vivi Egi Yunika; Eru Ahmadia (SAINTIS Publishing, 2025)
This study aims to analyze the influence of motivation and work spirit on the job satisfaction of Civil Servants (PNS) at the PUPRPRKP Office of Kubu Raya Regency. The research uses an associative quantitative approach with 92 respondents selected through a saturated sampling technique. Data were collected through questionnaires and interviews. The results of the regression analysis show the equation Y = 1.292 + 0.274X₁ + 0.348X₂, with a correlation coefficient (R) of 0.669, which indicates a strong relationship, and a determination value (R²) of 44.7%, indicating that 44.7% of the variation in job satisfaction is influenced by motivation and work spirit. The F-test results show that motivation and work spirit together have a positive and significant effect on job satisfaction. The partial t-test results show that motivation and work spirit have a positive and significant effect on job satisfaction. In conclusion, motivation and work spirit make a real contribution to increasing the job satisfaction of Civil Servants. This study recommends the need to strengthen motivation and work spirit through rewards, incentives, and a supportive work environment. Future research is expected to add other variables so that the results are more comprehensive.